Development opportunities for storing and displaying of spatial data in long-term experiments - Ragán, Péter (Acta Agraria Debreceniensis, 2016)
Long-term experiments are required to evaluate the impact of irrigation, nutrient utilization, and year factor as well as to assess the potential consequences of climate change. However, in the long-term experiment, it may be necessary to display spatial data for each parcel, either for investigation of soil heterogeneity or presentation. This article aims to provide help for researchers working in long-term experiments for storing and displaying spatial data. After the outlines of each experimental site were measured with GPS, a spatial database has been created in Quantum GIS. Then, a filter script in R statistical environment using RStudio graphical interface was written. The script helps avoid the QGIS data input interface so that large data can be attached to each parcel directly and as a result there is no need for a separate data entry, only the basic statistical database. The created GIS database can be used in many ways; it can be exported to KML file format that can be displayed using Google Earth. It is possible to view exported KML files in Google Drive with importing them to Google My Maps application, and with that a browser can display the map. With the Google Drive the maps can be shared within the research group, additionally the outlines can be edited and it is possible to upload the measurement data to the attributes table to existing empty table columns. The map created in Quantum GIS can be used for presentation purposes.